2022
DOI: 10.3390/cancers14071685
|View full text |Cite
|
Sign up to set email alerts
|

Breast Radiotherapy after Oncoplastic Surgery—A Multidisciplinary Approach

Abstract: Oncoplastic breast surgery encompasses a range of techniques used to provide equitable oncological outcomes compared with standard breast surgery while, simultaneously, prioritizing aesthetic outcomes. While the outcomes of oncoplastic breast surgery are promising, it can add an extra complexity to the treatment paradigm of breast cancer and impact on decision-making surrounding adjuvant therapies, like chemotherapy and radiotherapy. As such, early discussions at the multidisciplinary team meeting with surgeon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 138 publications
0
4
0
Order By: Relevance
“…Therefore, in all patients, but specifically in patients with an indication for boost therapy, the benefits of OPBCS should be discussed multidisciplinaryly, keeping both oncological and aesthetic outcomes in mind. Metz et al ( 57 ) reported on some crucial multidisciplinary recommendations when considering OPBCS:…”
Section: Radiotherapy After Opbcsmentioning
confidence: 99%
“…Therefore, in all patients, but specifically in patients with an indication for boost therapy, the benefits of OPBCS should be discussed multidisciplinaryly, keeping both oncological and aesthetic outcomes in mind. Metz et al ( 57 ) reported on some crucial multidisciplinary recommendations when considering OPBCS:…”
Section: Radiotherapy After Opbcsmentioning
confidence: 99%
“…Regarding breast cancer treatment, tumor characteristics, the type of surgical procedure, and chemo and RT can influence the breast cancer mortality ratio ( 3 ). Hence, the indication of RT after a total mastectomy in patients with positive lymph nodes decreases breast cancer mortality and distant/locoregional recurrence, contrary to patients with negative nodes ( 19 , 20 ).…”
Section: Basic Concepts In Breast Reconstructionmentioning
confidence: 99%
“…In the United States, 1 in 8 women will be diagnosed with invasive breast cancer, with an estimated 287,850,000 new cases diagnosed in 2022 ( 2 ). Surgery, radiation, and systemic treatment remain the crucial components of treatment, with approximately 8 out of 10 patients receiving ionizing radiation at some point ( 3 ). Additionally, breast reconstruction (BR) after mastectomy has improved patients’ satisfaction and well-being, reduced overall treatment costs, and provided better aesthetic results ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation